Geometric optimization of stepped spillways using genetic algorithm (Journal of Civil Engineering Researchers, 2023)
Recent advances in technology have created wide possibilities for building large dams, reservoirs and canals. These advances require the development of design and construction methods, especially for systems that can discharge sufficient flood. Shots and overflows are designed in such a way that no major damage is caused to the structure itself or to the surrounding environment to pass large flows through a hydraulic structure. During the flow of water over the spillway, it is necessary to consume some energy in order to prevent damage to the toe of the dam and its surroundings and finally to the dam itself. In this research, a method was presented to optimize the geometric parameters of the stepped overflow. For this purpose, using laboratory model data (275 tests in total). And the use of strong statistical software WEKA and MATLAB software obtained a formula to predict the amount of energy consumption. This formula was given to the genetic algorithm as an objective function. Entering the Yc/Hdam parameter, which includes both the flow rate and the total height of the dam, and the desired energy consumption value, this program is optimized by genetic algorithm and obtains the optimal number, length and width of steps. The results of this research show that: with the increase in flow rate, the amount of maximum energy consumption decreases, and with the increase of the head slope at a constant flow rate, the number of optimal steps for equal energy consumption increases.
Keywords: Genetic algorithm; optimization of geometric; energy dissipation; stepped spillways